Counseling on Healthy Home Ventilation as an Effort to Prevent the Transmission of Pulmonary TB at the Tanjung Beringin Community Health Center (JURNAL PENGMAS KESTRA (JPK), 2025)
Pulmonary tuberculosis (TB) is a contagious infectious disease that remains a serious challenge to improving public health in Indonesia. TB is transmitted through airborne droplets containing Mycobacterium tuberculosis, so the living environment, particularly the quality of home ventilation, plays a crucial role in preventing the spread of this disease. Inadequate ventilation can increase indoor germ density and increase the risk of transmission, especially in families living with TB sufferers. Therefore, promotive and preventive efforts are needed through public education regarding the importance of healthy home ventilation. This community service activity was held on October 3, 2025, from 9:00 a.m. WIB until completion in the Tanjung Beringin Community Health Center work area, with the aim of increasing public knowledge and awareness regarding the role of home ventilation in preventing the transmission of pulmonary TB. The activity implementation method included health education, interactive discussions, and practical demonstrations on how to optimize home ventilation, such as window arrangement, utilization of natural light, and good air circulation management. This activity involved 23 families, among whom there were TB patients. The results of the activity showed a significant increase in participant knowledge, with an average understanding achievement above 90% after participating in the counseling. In addition, participants expressed a willingness and commitment to implement improvements in home ventilation as a concrete step in preventing TB transmission. Overall, this community service activity made a positive contribution in supporting promotive and preventive efforts for pulmonary TB and has the potential to create a healthier and safer residential environment in the Tanjung Beringin Community Health Center work area.